Arenediazonium salts transformations in water media: Coming round to origins; Resource-Efficient Technologies; Vol. 2, iss. 1 - Trusova M. E. Marina Evgenievna; Kutonova K. V. Ksenia Valentinovna; Kurtukov V. V. Viktor Viktorovich; Filimonov V. D. Viktor Dmitrievich; Postnikov P. S. Pavel Sergeevich (2016, 2016)
Title screen